Ozone‐induced changes in the murine lung extracellular vesicle small RNA landscape. Issue 18 (23rd September 2021) - Smith, Gregory J.; Tovar, Adelaide; Kanke, Matt; Wang, Yong; Deshane, Jessy S.; Sethupathy, Praveen; Kelada, Samir N. P.
Abstract: Inhalation exposure to ozone (O3 ) causes adverse respiratory health effects that result from airway inflammation, a complex response mediated in part by changes to airway cellular transcriptional programs. These programs may be regulated by microRNAs transferred between cells (e.g., epithelial cells and macrophages) via extracellular vesicles (EV miRNA). To explore this, we exposed female C57BL/6J mice to filtered air (FA), 1, or 2 ppm O3 by inhalation and collected bronchoalveolar lavage fluid (BALF) 21 h later for markers of airway inflammation, EVs, and EV miRNA. Both concentrations of O3  significantly increased markers of inflammation (neutrophils), injury (total protein), and the number of EV‐sized particles in the BALF. Imagestream analysis indicated a substantial portion of particles was positive for canonical EV markers (CD81, CD51), and Siglec‐F, a marker of alveolar macrophages. Using high‐throughput small RNA sequencing, we identified several differentially expressed (DE) BALF EV miRNAs after 1 ppm (16 DE miRNAs) and 2 ppm (99 DE miRNAs) O3 versus FA exposure. O3 concentration‐response patterns in EV miRNA expression were apparent, particularly for miR‐2137, miR‐126‐3p, and miR‐351‐5p. Integrative analysis of EV miRNA expression and airway cellular mRNA expression identified EV miR‐22‐3p as a candidate regulator of transcriptomic responses to O3 in airway macrophages. In contrast, we did not identify candidate miRNA regulators of mRNA expression data from conducting airways (predominantly composed of epithelial cells). In summary, our data show that O3 exposure alters EV release and EV miRNA expression, suggesting that further investigation of EVs may provide insight into their effects on airway macrophage function and other mechanisms of O3 ‐induced respiratory inflammation. Abstract : Respiratory exposure to the common ambient air pollutant, ozone, causes airway inflammation and injury. Using high‐throughput RNA sequencing, we investigated whether ozone‐induced inflammation was associated with altered lung extracellular vesicle small RNA expression. We found that specific extracellular vesicle miRNAs, including miR‐22‐3p, were altered by ozone exposure that may affect the function of airway cells.